VD_FINDINFO Jug / 2012 / 80 vom 14. November 2011 - VD Tribunal cantonal (2011)
PEINE D'ENSEMBLE, REFORMATIO IN PEJUS, PEINE PRIVATIVE DE LIBERTÉ, TRAVAIL D'INTÉRÊT GÉNÉRAL, LEX MITIOR | 37 CP, 40 CP, 46 al. 1 CP, 49 CP, 115 LEtr